New Method for the Synthesis of Benzyl Alkyl Ethers Mediated by FeSO4 - Joshi, Girdhar; Adimurthy, Subbarayappa (Synthetic communications, 2011)
[image omitted] The synthesis of benzyl alkyl ethers from benzyl bromides and alcohols using FeSO4 as a recoverable and reusable mediator has been described without use of base and cosolvent under mild conditions.